Extension as expression of social responsibility for higher education - Marco, Ricardo Antonio de; Sarmento, Dirleia Fanfa; Menegat, Jardelino (Universidade Estadual de Campinas, 2016)
The National System of Higher Education Assessment 2004 in Axis 2, Institutional Development and its dimensions 1 and 3: Mission and Institutional Development Plan (IDP) and the Social Responsibility of the institution highlights the need for universities to incorporate in their activities teaching, research and extension practices that demonstrate their positive involvement in social development. In this sense, this article aims to evaluate the practice of university extension contributes to the consolidation of University Social Responsibility. was used as a method descriptive research and documentary analysis found that the institutional documents of the University of the West of Santa Catarina: mission, vision and values; Institutional Development Plan and the extension project of the University of Chapecó Best Age (UMIC); and the National System of Higher Education Evaluation. From this inference, it was revealed that UNOESC in its constitutive principles and official documents value-oriented civic education for social inclusion. It was found that the consolidation of MSW necessarily involves watchful eye of management to the principles of indivisibility of teaching, research and extension, components and ended the universities, which when not properly executed, counter and violate the legal provision; that inter- and transdisciplinary nature of extension projects, such as UMIC, have strong contribution to the consolidation of MSW; parallel, left clear that isolation Extension projects like UMIC not reach the fullness of the social commitment of universities, suggesting that inseparability is present with the incorporation of actions that promote social development.